Internet censorship detected in Iraq (Iraq) - Voidly (Voidly Global Censorship Index, 2026)
WARNING severity censorship detected in Iraq. Data sourced from CensoredPlanet.
Censorship Incident ID: IQ-2026-0195. Severity: warning. Confidence: 65%